Peasant Economy in Malaysia: The Advent of Capitalism and the Expansion of Money Economy into Agriculture in Colonial Malaya - A Rahman Tang Abdullah; Fazli Abd Hamid (2018)
This paper examines the advent of capitalism in rural economy by using the commercialization of the peasant economy in colonial Malaya period. It reflects the historical development with reference to the increase of money economy within the society who was mostly the peasants. It means that mostly all means of transaction exchanges were increasingly conducted in monetary form. Following this pattern, this phenomenon is applied to the years between 1850 and 1941 in Malaya as it was signified by the transition from traditional to modern orientation in the economic aspects of the Malay society with special attention to peasant community. Such economic changes that were manifested by the increase of money economy can be seen in a labour utilization and the change in land ownership, the commercial orientation in paddy cultivation, agricultural credit facilities and the penetration of commercialism in the Malay society as a whole.